Operation Barkhane and the future of intervention in the Sahel: The shape of things to come - Denis Tull (Stiftung Wissenschaft und Politik (SWP), 2021)
France is preparing to change its posture in the Sahel. After a 'mini surge' of 600 additional soldiers since February 2020, its counterterrorism Operation Barkhane is likely to revert to the presurge level, with more reductions possible in the medium term. Regardless of the details and timetable of the adjustments, French policy toward the Sahel is evolving as Paris seeks to balance a lighter military footprint with counterterrorism goals, the continued internationalization of intervention, and more local responsibility.
Keywords: 320